2021
DOI: 10.1155/2021/4888946
|View full text |Cite
|
Sign up to set email alerts
|

Bioinsecticide Production from Cigarette Wastes

Abstract: Tobacco, one of the most significant nonfood crops, is critical to agriculture worldwide. The tobacco processing business creates a significant amount of hazardous tobacco waste containing nicotine, and only a tiny portion of it gets recycled. Nicotine, the primary component of tobacco products such as cigarettes, is an alkaloid and can be used as an insecticide. This research aims to extract nicotine from discarded cigarette butts and utilize it as an insecticide. Extraction, emulsification, and efficiency te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In fact, nicotine was one of the first substances reported as a plant-derived agricultural insecticides. For the protection of crops and general well-being, it is viewed as a potential substitute for conventional insecticides 22 .…”
Section: Number Of Round-ragged Holes -------------------------------...mentioning
confidence: 99%
“…In fact, nicotine was one of the first substances reported as a plant-derived agricultural insecticides. For the protection of crops and general well-being, it is viewed as a potential substitute for conventional insecticides 22 .…”
Section: Number Of Round-ragged Holes -------------------------------...mentioning
confidence: 99%
“…The appropriate moisture content percent for efficient organic matter decomposition has been estimated between 40 and 65% (Ahmed et al 2019). Nevertheless, several organic substrates have different moisture percentages; Gudeta et al (2021) reported the low moisture content in TW. In this research, water content was within 35.2 and 60.2%, which is appropriate for microbial activity.…”
Section: Influence Of Process Parameters On Nicotine Degradation Rate...mentioning
confidence: 99%
“…e ANN model is capable of learning the pattern of the underlying process from prior data and generalizing the acquired information (or the complex mathematical relationship between input and output data). e ANN model is comprised of three distinct layers of input, hidden, and output layers known as neurons, which may be used to predict the connection between input and output layers [17]. All of the data are randomly divided into three categories: training (70%), testing (15%), and validation (15%).…”
Section: Artificial Neural Network (Ann) Modeling and Simulation Of E...mentioning
confidence: 99%